Lindane dissipation in a biomixture: Effect of soil properties and bioaugmentation - Sáez, Juliana María (2018)
The biomixture is the major constituent of a biopuriﬁcation system and one of the most important factors in its eﬃciency; hence the selection of the components is crucial to ensure the eﬃcient pesticides removal. Besides,bioaugmentation is an interesting approach for the optimization of these systems.A mixed culture of the fungus Trametes versicolor SGNG1 and the actinobacteria Streptomyces sp. A2, A5, A11,and M7, was designed to inoculate the biomixtures, based on previously demonstrated ligninolytic and pesticidedegradingactivities and the absence of antagonism among the strains. The presence of lindane and/or the inoculum in the biomixtures had no signiﬁcant eﬀect on the development of culturable microorganisms regardless the soil type. The consortium improved lindane dissipation achieving 81?87% of removal at 66 d ofincubation in the diﬀerent biomixtures, decreasing lindane half-life to an average of 24 d, i.e. 6-fold less than t1/2 of lindane in soils. However, after recontamination, only the bioaugmented biomixture of silty loam soil enhancedlindane dissipation and decreased the t1/2 compared to non-bioaugmented. The biomixture formulated with silty loam soil, sugarcane bagasse, and peat, inoculated with a fungal-actinobacterial consortium, could be appropriate for the treatment of agroindustrial eﬄuents contaminated with organochlorine pesticides in biopuriﬁcation systems.